2021
DOI: 10.1093/bib/bbab184
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of computational predictors for estimating protein stability changes upon missense mutations

Abstract: Understanding how a mutation might affect protein stability is of significant importance to protein engineering and for understanding protein evolution genetic diseases. While a number of computational tools have been developed to predict the effect of missense mutations on protein stability protein stability upon mutations, they are known to exhibit large biases imparted in part by the data used to train and evaluate them. Here, we provide a comprehensive overview of predictive tools, which has provided an ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…Another very relevant point is to which extent the methods are affected by \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\Delta \Delta G$\end{document} measures obtained outside physiological conditions. A recent paper [ 5 ] showed that there are some predictors in some extreme ranges of pH and temperature that decreases the performance. S669 dataset was divided into two parts: the former group containing variants whose temperature and pH are in physiological ranges \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$[293.15,313.15]$\end{document} K (20–40 \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$^\circ C$\end{document} ) and \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$[6.0,8.0]$\end{document} , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Another very relevant point is to which extent the methods are affected by \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$\Delta \Delta G$\end{document} measures obtained outside physiological conditions. A recent paper [ 5 ] showed that there are some predictors in some extreme ranges of pH and temperature that decreases the performance. S669 dataset was divided into two parts: the former group containing variants whose temperature and pH are in physiological ranges \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$[293.15,313.15]$\end{document} K (20–40 \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$^\circ C$\end{document} ) and \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}$[6.0,8.0]$\end{document} , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several challenges are of particular interest: (i) First, the slope of the regression line for predicted versus experimental ΔΔG values is much smaller than 1 for most methods and the range of the predicted ΔΔG values is narrower than the range of experimental values. 47,76,104 (ii) Almost all methods were trained on data with surplus of destabilizing mutations. 68,79 (iii) Hysteresis causes reverse mutations to not generally have simply inversed ΔΔG values.…”
Section: Data Set Biases: Destabilization and Mutation Typementioning
confidence: 99%
“…Generally, the predicting approaches can be divided into two categories, namely the statistics-based methods using machine learning (ML) and the structure-based methods using physical models (such as those applying force fields). Although the ML-based methods usually exhibit higher computational efficiency and accuracy compared with the physics-based approaches [ 14 , 15 ], these methods may usually suffer from the problems of difficulty for mechanism explanation. And the ML-based methods tend to show a limited scope of application due to the biased or limited training set.…”
Section: Introductionmentioning
confidence: 99%